À qui parlent les professionnels politiques ? - Sandrine Roginsky; Sophie Huys (Communication)
On September 7, 2010, the European Parliament voted in a resolution encouraging its members to use Web 2.0 technologies and “enter into a dialogue with the citizenry.” This article looks at the perceptions professional politicians develop regarding the audiences they believe they are reaching through digital multimedia platforms. The objective is twofold : to analyze these perceptions or representations and then to understand how such representations are constructed. The authors' objective is to contribute, in the field of politics, to a better understanding of the users and their uses of two specific digital platforms, Facebook and Twitter, through a longitudinal study over a period of five years (2009-2014).